PENGARUH PUPUK KASCING DAN HERBAFARM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS (Brassica oleraceae var. Capitata L.) - Miftahul Hidayah; Herman; Fathurrahman (DINAMIKA PERTANIAN, 2020)
ABSTRACT This study was conducted to examine the effect of interaction between Kascing and Herbafarm fertilizers on cabbage growth and yield. This study used a Factorial Completely Randomized Design consisting of 2 factors. The first factor was the application of kascing fertilizer (K) which consisted of 4 levels. The second factor was fertilization of Herbafarm (H) which consisted of 4 levels, so that this experiment had 16 treatment combinations. The parameters observed were the age of crop formation (days), crop diameter (cm), fresh weight of the crop (grams), and the number of leaves that not formed a crop (strands). The results showed that interaction of kascing fertilizer and Herbafarm was significantly affected on the crop diameter and fresh weight of cabbage crop heads. The best treatment was 1.8 kg of kascing fertilizer per plot and 75 ml of Herbafarm concentration per plant (K3H3). The main significant effect of kascing was found on the age of crop formation, crop diameter, fresh crop weight and number of leaves that not formed crop. The main significant effect of Herbafarm was found on the age of crop formation, crop diameter, fresh crop weight and number of leaves that not formed crop. The best treatment was 75 ml herbafarm per plant. Keywords: Kascing and Herbafarm fertilizers, Growth, Yield, Cabbage